Application of Cement Clinker as Ni-Catalyst Support for Glycerol Dry Reforming - Hua, Chyn Lee; Kah, Weng Siew; Jolius, Gimbun; Cheng, C. K. (Department of Chemical Engineering, Diponegoro University, 2013)
The increase in biodiesel production inevitably yield plethora of glycerol. Therefore, glycerol has been touted as the most promising source for bio-syngas (mixture of H 2 and CO) production. Significantly, coking on nickel-based catalysts has been identified as a major deactivation factor in reforming technology. Indeed, coke-resistant catalyst development is essential to enhance syngas production. The current work develops cement clinker (comprised of 62.0% calcium oxide)-supported nickel catalyst (with metal loadings of 5, 10, 15 and 20 wt%) for glycerol dry reforming (CO 2 ). Physicochemical characterization of the catalysts was performed using XRD, XRF, BET, TGA and FESEM-EDS techniques. Subsequently, reaction studies were conducted in a 7-mm ID fixed-bed stainless steel reactor at 1023 K with various CO 2 partial pressures at constant weight-hourly space velocity (WHSV) of 7.2×104 ml g cat -1 h . Gas compositions were determined using Agilent 3000 micro-gas chromatography (GC) and Lancom III gas analyzer. Results obtained showed an increment of BET surface area up to 32-fold with Ni loading which was corroborated by FESEM images. Syngas (H 2 and CO) ratios of less than 2 were being produced at 1023 K. A closer scrutiny to the transient profile revealed that the presence of CO 2 higher or lower than CGR 1:1 promotes the Boudouard reaction. © 2013 BCREC UNDIP. All rights reserved -1